2015
DOI: 10.1210/jc.2014-4159
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Status, Cardiac Function, and Mortality in Patients With Idiopathic Dilated Cardiomyopathy

Abstract: We found a clear association between thyroid dysfunction and increased risk of mortality in idiopathic dilated cardiomyopathy with HF. These results suggest that monitoring thyroid function in HF patients is necessary, and further studies on the treatment of HF with thyroid dysfunction are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 38 publications
3
31
0
4
Order By: Relevance
“…In this subclinical hyperthyroid group, the percentage of LGE-positive segments was significantly lower. This finding corresponds to an interesting result of our previous study in which the prevalence of atrial fibrillation was unexpectedly lower in the subclinical hyperthyroid group than in other thyroid states4. At that time, a possible explanation was given that usage of beta-blockers in our cohort was more frequent, thus blunting the potential pathophysiological effects of subclinical hyperthyroidism.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this subclinical hyperthyroid group, the percentage of LGE-positive segments was significantly lower. This finding corresponds to an interesting result of our previous study in which the prevalence of atrial fibrillation was unexpectedly lower in the subclinical hyperthyroid group than in other thyroid states4. At that time, a possible explanation was given that usage of beta-blockers in our cohort was more frequent, thus blunting the potential pathophysiological effects of subclinical hyperthyroidism.…”
Section: Discussionsupporting
confidence: 89%
“…This subgroup belongs to a cohort study of 458 IDCM patients previously reported4. The study disposition is showed in Supplementary Figure S1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This correlation though did not exist with levels of T4 or TSH. At the clinical level there is correlation between low levels of T3 and idiopathic dilated cardiomyopathy [12]. …”
Section: Geneticsmentioning
confidence: 99%
“…But more importantly, some studies suggest that more than 90% of patients with overt hypothyroidism and some patients with subclinical hypothyroidism can have derangements of the lipid profile, including low density lipoproteins (LDL) and apolipoprotein A. Treatment with thyroid hormones can lead to reversal of these derangements [10]. …”
Section: Geneticsmentioning
confidence: 99%